Fifty years of data show the effects of climate on overall skull size and the extent of seasonal reversible skull size changes (Dehnel's phenomenon) in the common shrew. Issue 10 (27th October 2022) - Taylor, Jan R. E.; Muturi, Marion; Lázaro, Javier; Zub, Karol; Dechmann, Dina K. N.
Abstract: Global climate change affects many aspects of biology and has been shown to cause body size changes in animals. However, suitable datasets allowing the analysis of long‐term relationships between body size, climate, and its effects are rare. The size of the skull is often used as a proxy for overall body size. Skull size does not change much in fully grown vertebrates; however, some high‐metabolic small mammals shrink in winter and regrow in spring, including their skull and brain. This is thought to be a winter adaptation, as a smaller brain size reduces energy requirements. Climate could thus affect not only the overall size but also the pattern of the size change, that is, Dehnel's phenomenon, in these animals. We assessed the impact of the changes in climate on the overall skull size and the different stages of Dehnel's phenomenon in skulls of the common shrew, Sorex araneus, collected over 50 years in the Białowieża Forest, E Poland. Overall skull size decreased, along with increasing temperatures and decreasing soil moisture, which affected the availability of the shrews' main food source, earthworms. The skulls of males were larger than those of females, but the degree of the decrease in size did not differ between sexes. The magnitude of Dehnel's phenomenon increased over time, indicating an increasing selection pressure on animals in winter. Overall, climate clearly affected the common shrew's overall size as well as its seasonal size changes. With the current acceleration in climate change, the effects on the populations of this cold‐adapted species may be quite severe in a large part of its distribution range. Abstract : We assesed the impact of the changes in climate on the overall skull size (the proxy of the overall body size) and the seasonal changes of skull height (Dehnel's phenomenon) in skulls of the common shrew, Sorex araneus, collected over 50 years in the Białowieża Forest, NE Poland. Overall skull size decreased, along with increasing temperatures and decreasing soil moisture, which determined the availability of the shrews' main food source, earthworms. The magnitude of Dehnel's phenomenon increased over time, indicating an increasing selection pressure on animals in winter.